Global polarization of Λ hyperons in Au + Au collisions at sNN =200 GeV - STAR Collaboration (Physical Review C, 2018)
Global polarization of Λ hyperons has been measured to be of the order of a few tenths of a percentage in Au+Au collisions at sNN = 200 GeV, with no significant difference between Λ and Λ. These new results reveal the collision energy dependence of the global polarization together with the results previously observed at sNN = 7.7-62.4 GeV and indicate noticeable vorticity of the medium created in noncentral heavy-ion collisions at the highest Relativistic Heavy Ion Collider collision energy. The signal is in rough quantitative agreement with the theoretical predictions from a hydrodynamic model and from a multi-phase transport model. The polarization is larger in more peripheral collisions, and depends weakly on the hyperon's transverse momentum and pseudorapidity ηH within |ηH|<1. An indication of the polarization dependence on the event-by-event charge asymmetry is observed at the 2σ level, suggesting a possible contribution to the polarization from the axial current induced by the initial magnetic field. © 2018 American Physical Society.
181 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed